Learning community management in strengthening differentiated learning for teachers of Tambakrejo 01 Elementary School, Gayamsari, Semarang City - Karima, Ida; Wuryandini, Endang; Prayito, Muhammad (Educenter : Jurnal Ilmiah Pendidikan, 2025)
This study aims to examine learning community management in strengthening differentiated learning for teachers at Tambakrejo 01 Elementary School, Gayamsari, Semarang City. The background of this research is based on the urgency of improving teachers' pedagogical competence in responding to the implementation of the Merdeka Curriculum, especially in designing and implementing differentiated learning in accordance with students' learning readiness, interests, and learning profiles. The approach used is descriptive qualitative with data collection techniques through participatory observation, semi-structured interviews, and documentation. Data analysis was conducted using the Miles and Huberman interactive model, including data reduction, data presentation, and conclusion drawing. The results showed that learning community management in the school has been effectively implemented, including careful planning, participatory organization, consistent implementation, and reflective evaluation. Teachers are active in developing differentiated teaching modules, diagnostic assessment, and joint reflection. The learning community contributes significantly to improving teacher competence and transforming learning practices to be more adaptive, equitable, and learner-centered. This study concludes that effective learning community management is a key strategy in implementing differentiated learning and realizing Merdeka Curriculum in elementary schools.